2000
DOI: 10.1111/j.1151-2916.2000.tb01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Oxide Structure Prepared by the Sol–Gel Route: I, The Role of the Alcoholic Solvent

Abstract: Sol-gel-derived powder samples of zirconia (ZrO 2 ) prepared via the dissolution of zirconium n-propoxide in methanol, ethanol, and 2-propanol have been characterized mainly using perturbed angular correlations spectroscopy, as a function of temperature. Results indicate that the nanostructures and subsequent thermal evolution are alcohol dependent: the shorter the alcohol chain, the more hydrolyzed the product. ZrO 2 powder that has been obtained using ethanol as the solvent is the product that exhibits the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…The precipitation is completed when the equivalence point (pH¼ 9) is reached. Caracoche et al [46] suggested that slight acidification of the solution of alkoxides by nitric acid induces the shift of zirconia crystallization to low-temperature region. This data is in crystallization of the metastable zirconia in acidic medium due to the excess free energy [47].…”
Section: Effect Of Preparation Conditions On Phase Of Lizr and Its Camentioning
confidence: 99%
“…The precipitation is completed when the equivalence point (pH¼ 9) is reached. Caracoche et al [46] suggested that slight acidification of the solution of alkoxides by nitric acid induces the shift of zirconia crystallization to low-temperature region. This data is in crystallization of the metastable zirconia in acidic medium due to the excess free energy [47].…”
Section: Effect Of Preparation Conditions On Phase Of Lizr and Its Camentioning
confidence: 99%
“…At 728 K a sharp exothermic effect with an enthalpy Q of 111.3 J/g was detected. This effect corresponds to the phase transition of the material from the amorphous to crystalline state [23][24][25]. At temperatures higher than 873 K, no exothermal effects were detected.…”
Section: Resultsmentioning
confidence: 90%
“…During heating from 873 to 1508 K, the mass of the sample continued to decrease but the mass loss was negligible (0.86%). This can be associated with the elimination of the residual OH groups from the material [25,26]. After annealing at temperatures higher than T S = 1508 K, the mass remained constant.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…1, January 2007, pp. [41][42][43][44][45][46] 2007, DESIDOC 41 cationic doping using hydrothermal processes, and sol-gel processes [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%